Peningkatan Pengetahuan Klien tentang HIV/AIDS melalui Edukasi Audiovisual - Lamma, Nirwana Alef; Peristiowati, Yuly (Yayasan Inspirasi El Burhani, 2026)
Introduction: Education about HIV/AIDS is a crucial component in strengthening prevention and control efforts within Voluntary Counseling and Testing (VCT) services. Observations in the VCT Clinic of Elim Hospital Rantepao revealed that education was mainly delivered verbally without routine use of audiovisual media, resulting in less effective engagement and comprehension among clients. Objective: This community service activity aimed to improve clients’ knowledge about HIV/AIDS through the implementation of educational video media at the VCT Clinic of Elim Hospital Rantepao. Methods: The activity applied an educational and participatory approach including a 4-minute HIV/AIDS video covering definition, transmission, prevention, VCT testing, ARV therapy, and stigma reduction. Knowledge was measured using a pre-test and post-test questionnaire consisting of 10 items. Situation analysis was also performed using Fishbone analysis to identify root causes of educational gaps, SWOT analysis to map potential implementation strategies, and USG (Urgency, Seriousness, Growth) analysis to determine priority issues. A total of 20 clients participated (60% female; aged 17–45 years). Results: The intervention led to a significant increase in clients’ knowledge, with the mean score rising from 6.0 in the pre-test to 8.7 in the post-test, reflecting a 23.75% improvement. Positive shifts were also observed in attitudes toward PLWHA, with a 20% increase in attitude-related indicators. Client satisfaction was high, with 95% reporting satisfied or very satisfied experiences. Fishbone and USG analysis identified the lack of audiovisual educational media as the top priority problem (score 14), while SWOT analysis strengthened the feasibility of sustainable implementation based on service support and community opportunities. Conclusion: Educational videos are proven to be an effective and well-accepted health promotion tool to improve HIV/AIDS knowledge and reduce stigma among VCT clinic clients. This intervention is recommended for continuous use as an innovative strategy to enhance the quality of health education and support HIV/AIDS prevention efforts in the community.